Self-assembly and regulation of protein cages from pre-organised coiled-coil modules - Fabio Lapenta (Nature Portfolio, 2021)
Coiled-coil protein origami is a strategy for the de novo design of polypeptide nanostructures based on coiled-coil dimer forming peptides, where a single chain protein folds into a polyhedral cage. Here, the authors design a single-chain triangular bipyramid and also demonstrate that the bipyramid can be self-assembled as a heterodimeric complex, comprising pre-defined subunits.